2015
DOI: 10.1183/09031936.00216914
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of pulmonary lipid homeostasis drives cigarette smoke-induced lung inflammation in mice

Abstract: Overwhelming evidence links inflammation to the pathogenesis of smoking-related pulmonary diseases, especially chronic obstructive pulmonary disease (COPD). Despite an increased understanding of the disease pathogenesis, mechanisms initiating smoking-induced inflammatory processes remain incompletely understood.To investigate the mechanisms that initiate and propagate smoke-induced inflammation, we used a wellcharacterised mouse model of cigarette smoke exposure, mice deficient for interleukin (IL)-1α, IL-1β a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 25 publications
3
73
0
Order By: Relevance
“…Mouse spleen and house-dust mite exposed lung tissues were used as positive controls for CD21 and Ki67 staining, respectively. Consistent with previous reports [11,12], we showed that foamy macrophages (green arrows) were located in close proximity to the lymphoid aggregates ( Fig. 3e).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Mouse spleen and house-dust mite exposed lung tissues were used as positive controls for CD21 and Ki67 staining, respectively. Consistent with previous reports [11,12], we showed that foamy macrophages (green arrows) were located in close proximity to the lymphoid aggregates ( Fig. 3e).…”
Section: Resultssupporting
confidence: 93%
“…However, B cell-deficient mice are completely protected from chronic smokeinduced lymphoid aggregate formation and do not develop emphysema [8]. These aggregates are often surrounded by foamy macrophages that are thought to contain cigarette smoke-induced lipid oxidation products [11] and associate with chronic inflammatory processes [12]. The role of sex and specifically female sex hormones in the pathogenesis of lymphoid follicles in small airways has not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This is best exemplified by the rare disease pulmonary alveolar proteinosis, in which disrupted granulocyte macrophage-colony stimulating factor signaling, most commonly caused by autoantibodies, is associated with surfactant accumulation and AM immune dysfunction (14). However, the intriguing finding of increased AM "foam cells" (abnormal lipidladen AMs) in a wide range of human lung disorders (15) and rodent inhalational exposures (16,17) suggests the provocative possibility that coordinate AM dysfunction and surfactant dysregulation may play a role in a final common pathway in the pathogenesis of common chronic lung diseases and environmental exposures.…”
Section: Brief Overview Of the Unique Composition And Life Cycle Of Smentioning
confidence: 99%
“…Smoking is a major risk factor for chronic obstructive pulmonary disease, interstitial lung diseases, and all types of lung cancer, especially squamous cell lung cancer. Smoking exposure rapidly leads to lipid accumulation in pulmonary macrophages, a condition associated with abnormal lung physiology, including dysregulated pulmonary innate and adaptive immune responses to the environment (8). Abnormal lipid metabolism such as increase in total and esterified cholesterol, increased fatty acid synthesis, and accumulation of lipidloaded macrophages (9)(10)(11)(12)(13) are characteristic of lung cancer.…”
mentioning
confidence: 99%